PENGARUH KECANDUAN SISWA TERHADAP GAME ONLINE (STUDI TENTANG KEBIASAAN SISWA BERMAIN GAME ONLINE) DI SMP N 3 TELUK KUANTAN - Edrizal Edrizal (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The type of research used is qualitative research using field research types, the subjects in the study were students of SMP N 3Teluk Kuantan. While the method of data collection uses observation and interview techniques to obtain the information needed,then analyzed and described in written form. The results of this study indicate that the effects that arise due to addiction playonline games for students who are addicted including: 1) more time spent at the computer or internet cafe with a longerduration. 2) time to play more so you can forget about their time to study. 3) lack of attention to the health condition of theirbody (staying up late). 4) causing a sense of laziness for school and a decrease in grades in school. That's some of the effectsthat can be caused if someone who is addicted to too much opium with online games. These effects seemed to makethemselves become abnormal people. Because someone who is addicted to online games feels they have failed to give goodservice to their lives.